PATTERN OF FRESH FRUIT BUNCH (FFB) PRODUCTION AND YIELD DISTRIBUTION OF OIL PALM IN ANDHRA PRADESH - P. MADHAVI LATHA *, M. TIRUPATI REDDY, B. PRATAP and H.P. MAHESWARAPPA, (The Journal of Research ANGRAU, 2021)
The field study was conducted to evaluate new tenera hybrids at Horticultural Research Station,Vijayarai. As oil palm is a continuous fruit yielding crop in a harvest year, variations in month wise FFBproduction was studied in tenera hybrid crosses. The performance of hybrids under irrigated conditionsplanted during 2007 was studied for four years (9 to 12 years after planting) for bunch number,bunch weight and FFB production per ha at monthly intervals. During the four years of study, palmsshowed significant differences in bunch number, average bunch weight and FFB production in differentmonths of a harvest year. Average bunch weight increased with increase in age of the palms duringthe study period from 6th to 9th harvest years (11.54 to 14.98 kg) with inverse relation between numberof bunches produced per palm and average bunch weight. May, August and September were themonths which recorded 40-45 % of total yield of a harvest year while November, December, Januaryand February were the lean production months which recorded lower number of bunches palm-1month-1(0.5) and lower bunch weights month-1 (4 to 5 kg) contributing to 10 % annual yield. Cumulativeyield of 4 years data shows that there was 18 % and 15% FFB production recorded in May andAugust months, respectively. Four years mean FFB production was 3.5 t ha-1 in August followed by 3t ha-1 in May month. In lean production months (November, December, January and February) permonth FFB production was only 0.5 t ha-1. In Andhra Pradesh, peak oil palm FFB production seasonis 6 months (April to September) and the remaining 6 months (October to March) is lean period.